Economic Fluctuation and Public Health Financing in Brazil - Matosinhos, Lívia Aladim (2022)
The Brazilian public health system, officially known as Sistema Único de Saúde (SUS), has long been characterized by insufficient funding and irregular flow of resources. The system is jointly financed by the federal, state and municipal governments, but some imbalance is observed as tax revenue is concentrated at the federal level, while health services are mainly provided at the municipality level. The mismatch between financing capacity and the provision of public health services can influence the financial resilience of SUS in the face of external shocks, such as the economic recession that affected Brazil in 2015-2016. In this sense, the present study investigated the relationship between economic fluctuation and public health financing in Brazil. Specifically, three separate yet complementary articles were developed. In the first article, the scientific production on public health and the 2015-2016 economic recession in Brazil was systematically reviewed, revealing a possible gap in the literature due to the lack of applied studies focusing on the influence of the 2015-2016 economic recession on the financing of public health services in Brazil. In the second article, a trend analysis was carried out to evaluate the financial resilience of the SUS to the 2015-2016 economic recession and the results indicate that the crisis may have negatively influenced the evolution of public health financing in most of Brazilian municipalities. In the third and last article, the use of an instrumental variables approach provided evidence that public health financing is pro-cyclical in Brazil. Based on these findings, two main conclusions were made. First, the mismatch between tax revenue and service provision faced by municipalities gives extra importance to intergovernmental health transfers. Second, the pro-cyclical behavior of public health financing may hinder the construction of a financially resilient health system in Brazil. Keywords: Economic Fluctuation. Public Health Financing. Brazil.